Penyuluhan Bahaya Kemasan Pangan terhadap Kesehatan dan Lingkungan bagi Warga Dusun IV Muara Jalai, Kampar Utara - Anna Dhora; Razita Hariani; Ardiansyah Hamid; Fajar Aga W; Niken Ellani P (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The use of food packaging provides various benefits such as protecting products, extending shelf life, facilitating distribution, and becoming a promotional medium for producers and information for consumers. However, not all packaging materials are safe due to the use of chemicals and improper use practices, which can endanger public health. In addition, the use of single-use packaging causes environmental problems due to the accumulation of inorganic waste. Residents of Muara Jalai Hamlet IV also face similar concerns related to the safety of food packaging and the increasing volume of waste from daily activities. Therefore, the PKM Team of the TPKS Study Program of Kampar Polytechnic carried out an extension activity entitled "Counseling Regarding Potential Dangers in Food Packaging for Residents of Hamlet IV of Muara Jalai Village, North Kampar District, Kampar Regency". This activity succeeded in increasing citizens' knowledge about the dangers of food packaging materials, as well as encouraging the implementation of safer and more environmentally friendly packaging alternatives. In addition, counseling participants were invited to understand how to recognize plastic codes, choose natural-based packaging, and apply reduce, reuse, and recycle habits. With this activity, the community is expected to be wiser in using food packaging and play an active role in preserving the environment.